HUBUNGAN PENGETAHUAN IBU TENTANG MENYUSUI DENGAN SIKAP PEMBERIAN ASI EKLUSIF DI DESA UKIRSARI - Naziah Prihandini, (2020)
The United Nations Children's Fund (UNICEF) and the World Health Organization (WHO) receive exclusive breastfeeding assistance for up to six months. Objective: This study was conducted to find out the description of mothers associated with exclusive breastfeeding attitudes. Method: This study uses a descriptive research method, with research research breastfeeding mothers who reside in the village of Ukirsari. The sampling method used was purposive sampling. The data collection method used was a questionnaire. Results: The results of the study obtained knowledge of mothers about exclusive breastfeeding as many as 57 respondents 93.5% obtained good knowledge while 4 respondents 7.0% had an attitude of exclusive breastfeeding that was not good. While of 36 respondents 63.9% had poor knowledge, there were 23 respondents 36.1% had good exclusive breastfeeding ownership. Pvalue (0.001). Conclusion: Most of the mothers in the village of Ukirsari have a good level of knowledge and a good attitude.